Dietary intake of fiber in relation to knee pain trajectories - Dai, Zhaoli (Arthritis Care Res (Hoboken), 2017)
OBJECTIVE: Dietary fiber may reduce knee pain in part by lowering body weight and inflammation. In this study, we assessed whether fiber intake was associated with knee pain development patterns. METHODS: In a prospective, multicenter cohort of 4,796 men and women aged 45-79 years with or at risk of knee osteoarthritis in Osteoarthritis Initiative, participants were followed up annually for 8 years. Dietary fiber was estimated using a validated food frequency questionnaire at baseline. Group-based trajectory modeling was used to identify WOMAC pain trajectories, which were assessed for the associations with dietary fiber intake using polytomous regression models. RESULTS: Of the 4,470 eligible participants (8,940 knees) [mean age: 61.3 (SD: 9.1) years, 58% women], 4.9% underwent knee replacement and were censored at the time of surgery. Four distinct knee pain patterns were identified: no pain (34.5%), mild pain (38.1%), moderate pain (21.2%) and severe pain (6.2%). Dietary total fiber was inversely related to membership in the moderate or severe pain group (both p for trend ≤0.006). Subjects in the highest versus lowest quartile of total fiber had lower risks of belonging to moderate pain (OR=0.76, 95% CI: 0.61, 0.93) and severe pain patterns (OR=0.56, 95% CI: 0.41, 0.78). Similar results were found for grain fiber with these two pain patters. CONCLUSION: Our findings suggest that high dietary total or grain fiber, particularly in the recommended daily fiber average intake of 25g per day, was associated with lower risks of belonging to moderate and severe knee pain development patterns over time.